2018
DOI: 10.5045/br.2018.53.4.314
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between liver iron concentration determined by R2-MRI, serum ferritin, and liver enzymes in patients with thalassemia intermedia

Abstract: BackgroundIron overload is a risk factor affecting all patients with thalassemia intermedia (TI). We aimed to determine whether there is a relationship of serum ferritin (SF) and alanine aminotransferase (ALT) with liver iron concentration (LIC) determined by R2 magnetic resonance imaging (R2-MRI), to estimate the most relevant degree of iron overload and best time to chelate in patients with TI.MethodsIn this cross-sectional study, 119 patients with TI (mean age years) were randomly selected and compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…Patients with TI usually have high iron content loading in their tissues as evidenced by other studies from different areas of the world 13 , 20 , 21 . Our sample of patient had even higher iron content, which is in line with other reports from Middle East 3 , 14 . This might be due to compliance deterioration, background cultural beliefs, possible side effects of iron chelating drugs, and the frequent use of mimic medications in this part of the world 22 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Patients with TI usually have high iron content loading in their tissues as evidenced by other studies from different areas of the world 13 , 20 , 21 . Our sample of patient had even higher iron content, which is in line with other reports from Middle East 3 , 14 . This might be due to compliance deterioration, background cultural beliefs, possible side effects of iron chelating drugs, and the frequent use of mimic medications in this part of the world 22 .…”
Section: Discussionsupporting
confidence: 93%
“…Physicians have several challenges when using medications that eliminate excessive iron, including type, dose, expected adverse effects, and the best time to start an iron chelator. Therefore, the need for a naturally mediated iron chelator based on plants is increasing along with the increase of thalassemia patients around the world [13][14][15] . Green tea (GT) seems to be one of the best available options due to its natural properties to counteract iron absorption in addition to other promising advantages 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…However, other reports did not find a significant relationship between endocrine disorders and serum ferritin level [ 21 , 22 ].. The serum ferritin level could estimate the liver iron concentration in TM [ 23 ]. Moreover, Sobhani et al [ 24 ] found that higher serum ferritin strongly predicted the severity of cardiac and liver iron overload.…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that postmenopausal osteoporosis (PMOP) is mainly caused by the decline of estrogen, and is usually treated with estrogen replacement therapy. Interestingly, increasing studies have revealed that levels of serum ferritin are promoted by more than twofold after menopause and the abnormal iron accumulation (IA) contributes significantly to PMOP development 2–5 . Therefore, it is of great significance to explore the molecular mechanism by which IA regulates osteoporosis pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, increasing studies have revealed that levels of serum ferritin are promoted by more than twofold after menopause and the abnormal iron accumulation (IA) contributes significantly to PMOP development. [2][3][4][5] Therefore, it is of great significance to explore the molecular mechanism by which IA regulates osteoporosis pathogenesis. This will provide benefits for the development of alternative therapeutic targets or strategies for osteoporosis treatment.…”
Section: Introductionmentioning
confidence: 99%